UPLC-MS/MS Determination of Linezolid and Heme in Plasma of Infected Patients and Correlation Analysis - Wang, Yingying; Ye, Xuemei; Lan, Qin; Ke, Xiaofang; Hu, Lufeng; Hu, Lichuan (BioMed research international, 2021)
Linezolid can cause serious haematological toxicity, such as thrombocytopenia and aneamia. Heme, composed of iron and porphyrin, is an important component of hemoglobin. In order to investigate the relationship between the concentration of linezolid and heme in the plasma of infected patients, a UPLC-MS/MS method that can determine the concentrations of linezolid and heme simultaneously was developed and validated. A total of 96 healthy subjects and 81 infected patients, who received blood routine blood tests, were included and determined by the UPLC-MS/MS method. The results showed that the concentration of linezolid was 5.08±3.46 μg/mL in infected patients who were treated with linezolid. The heme in healthy subjects was 7.05±8.68 μg/mL, and it was significantly decreased to 0.88±0.79 μg/mL in infected patients (P<0.01). Spearman correlation analysis showed that linezolid had a high negative correlation with platelet (PLT) (R=−0.309). Heme had a high positive correlation with hemoglobin (Hb) (R=0.249) in healthy subjects and infected patients. The ROC analysis showed that heme had diagnostic value to distinguish low Hb (110 g/L). In conclusion, there was a positive correlation between heme and Hb, and this correlation was also observed in infected patients. A high concentration of linezolid was inclined to decrease PLT. Monitoring of heme and linezolid helps in the early diagnose of low Hb and PLT.